Critical thinking in Chinese higher education: a case study of knowledge transfer - Li, Ruijing (2017)
The issue of critical thinking (CT) amongst Chinese students has emerged as an important topic among educators. While there is some literature on CT and Chinese students’ performance, no study has tackled how this increasing focus on CT is impacting on higher education in China and what CT means to policy makers, teachers and students. This thesis sets out to fill this gap using insights from the theory of knowledge transfer. This theoretical framework was chosen in order to examine the ways in which Western CT theory and practice is gradually being imported to and integrated into Chinese culture, largely focusing on the understanding of CT. Using a case study approach, the thesis reports on empirical findings that have emerged from analysing Chinese Ministry of Education press releases and mission statements, observing university CT classes and studying chats about CT on a student internet discussion forum. Findings show that: 1. some core aspects of modern Western approaches to CT, such as how to deal with uncertainty, are missing in Chinese teaching; 2. disposition and emotion are sidelined in favour of a strong focus on logic and reason, and their inseparable relationship to reasoning ability found by Western scholars was neglected. 3. CT is regarded as crucial by Chinese educators and students but currently the teaching fails to make CT accessible and interesting to students and might therefore not foster CT itself. These findings have important implications for how policy makers and educators might continue to implement and teach CT in China.